The Analgesic Efficacy of Intraperitoneal Ropivacaine Versus Bupivacaine for Laparoscopic Cholecystectomy: a Meta-Analysis - Xu, Tao; Dong, Buhuai; Wu, Xucai; Shi, Chuan; Huang, Liangku; Zhou, Li (Zentralblatt für Chirurgie - Zeitschrift für Allgemeine, Viszeral-, Thorax- und Gefäßchirurgie, 2022)
Introduction This meta-analysis aimed to compare the analgesic efficacy of intraperitoneal ropivacaine versus bupivacaine for laparoscopic cholecystectomy.Methods We searched PubMed, EMbase, Web of Science, EBSCO, and Cochrane Library databases from inception through January 2020 and included randomized controlled trials (RCTs) evaluating the analgesic efficacy of ropivacaine versus bupivacaine for laparoscopic cholecystectomy.Results Five RCTs are included in the meta-analysis. In patients with laparoscopic cholecystectomy, ropivacaine and bupivacaine demonstrated comparable pain scores at 2 h (SMD = –0.22; 95% CI = –0.54 to 0.10; p = 0.18), 4 h (SMD = –0.16; 95% CI = –0.42 to 0.10; p = 0.22), 8 h (SMD = –0.60; 95% CI = –1.19 to –0.01; p = 0.05), and 24 h (SMD = 0.33; 95% CI = –1.19 to 1.84; p = 0.67), as well as time to first analgesic requirement (SMD = 0.10; 95% CI = –0.23 to 0.42; p = 0.56).Conclusions Intraperitoneal ropivacaine and bupivacaine have a similar analgesic efficacy for laparoscopic cholecystectomy.
Keywords: endovaskuläre Therapie; interventionelle Endoskopie; minimal residual disease